Paradigma Kesehatan Masyarakat dalam Pelayanan Persalinan Berbasis Kearifan Lokal: Integrasi Praktik Budaya dan Evidence-Based Midwifery untuk Meningkatkan Keselamatan Ibu dan Bayi - Arif, Wahyuni (Jurnal Ragam Pengabdian, 2026)
Integrating safe cultural practices with evidence-based midwifery care is a promising strategy for improving maternal and neonatal health outcomes while maintaining community acceptance and clinical safety. This systematic literature review, guided by PRISMA 2020 and the PICOS framework, searched Scopus, PubMed, and Science Direct screening 4,523 articles, resulting in 20 articles that met inclusion criteria that met inclusion criteria for narrative-thematic synthesis, drawing on qualitative research, mixed-methods studies, implementation research, program evaluations, systematic reviews, and meta-analyses. Findings show that combining local wisdom with evidence-based midwifery improves access to maternal health services, patient satisfaction, continuity of care, quality of care, and referral outcomes. Implementation models such as Birthing on Country, Indigenous Midwifery, Ngarrama Maternity Service, midwife–traditional birth attendant partnerships, and Respectful Maternity Care strengthened community trust and service acceptance, with success depending on providers' cultural competence, community engagement, supportive policy, functioning referral systems, and cross-sector collaboration, while limited regulation, resource constraints, and stigma toward traditional practices remained key barriers. The study concludes that integrating local wisdom into evidence-based midwifery enables woman-centered, culturally responsive care without compromising safety, calling for stronger policy support, provider training in cultural competence, and deeper partnership with local communities.